Risk factors for colorectal cancer significantly vary by anatomic site - Samir Gupta; Lin Liu; Joshua Demb; Ashley Earles; María Elena Martínez; Ranier Bustamante; Alex K Bryant; James D Murphy (BMJ Open Gastroenterology)
Objective To conduct an anatomic site-specific case–control study of candidate colorectal cancer (CRC) risk factors.Design Case–control study of US veterans with >1 colonoscopy during 1999–2011. Cases had cancer registry-identified CRC at colonoscopy, while controls were CRC free at colonoscopy and within 3 years of colonoscopy. Primary outcome was CRC, stratified by anatomic site: proximal, distal, or rectal. Candidate risk factors included age, sex, race/ethnicity, body mass index, height, diabetes, smoking status, and aspirin exposure summarised by adjusted ORs and 95% CIs.Results 21 744 CRC cases (n=7017 rectal; n=7039 distal; n=7688 proximal) and 612 646 controls were included. Males had significantly higher odds relative to females for rectal cancer (OR=2.84, 95% CI 2.25 to 3.58) than distal cancer (OR=1.84, 95% CI 1.50 to 2.24). Relative to whites, blacks had significantly lower rectal cancer odds (OR=0.88, 95% CI 0.82 to 0.95), but increased distal (OR=1.27, 95% CI 1.19 to 1.37) and proximal odds (OR=1.62, 95% CI 1.52 to 1.72). Diabetes prevalence was more strongly associated with proximal (OR=1.29, 95% CI 1.22 to 1.36) than distal (OR=1.15, 95% CI 1.08 to 1.22) or rectal cancer (OR=1.12, 95% CI 1.06 to 1.19). Current smoking was more strongly associated with rectal cancer (OR=1.81, 95% CI 1.68 to 1.95) than proximal cancer (OR=1.53, 95% CI 1.43 to 1.65) or distal cancer (OR=1.46, 95% CI 1.35 to 1.57) compared with never smoking. Aspirin use was significantly more strongly associated with reduced rectal cancer odds (OR=0.71, 95% CI 0.67 to 0.76) than distal (OR=0.85, 95% CI 0.81 to 0.90) or proximal (OR=0.91, 95% CI 0.86 to 0.95).Conclusion Candidate CRC risk factor associations vary significantly by anatomic site. Accounting for site may enable better insights into CRC pathogenesis and cancer control strategies.